Analiasa Bentuk-bentuk Konflik dalam Lingkungan Kerja. - Kasirul Fadli; Manja Asmira; Rohid Nurfadillah; Anggil Risnawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In the work environment, employees definitely have different identities such as origin, religion, ethnicity and education. However, these differences do not affect the condition of the company unless accompanied by bad behavior from the employees employed there. Inappropriate behavior disrupts communication and communication effectiveness. This creates conflict between employees in both horizontal and vertical relationships. conflict is a dispute between two or more parties who argue due to lack of status or resources and attempt to control or control each other through damage, loss, or other controlled means, resulting in the following consequences Damaging the relationship between the parties. Forms of conflict that often occur in the work environment, namely interpersonal conflict, conflict between groups, and conflict between parts of the organization. Conflict can create positive and negative impacts in the work environment. Conflict can be controlled with appropriate conflict management strategies, one of which is using a conflict management strategy with the Interest-Based Relational Approach (IBRA) introduced by Fisher and Ury, namely by (1) Separating people from problems, (2) Focusing on interests, not a position, (3) Invent options for mutual gain, and (4) Insist on using Objective criteria. By implementing the right strategies, conflict can become an opportunity for organizations to innovate, improve internal processes, and build stronger relationships among employees.